Bruton's Tyrosine Kinase Is Required for Activation of Iκb Kinase and Nuclear Factor κb in Response to B Cell Receptor Engagement - Petro, James B. (The Rockefeller University Press, 2000)
Mutations in the gene encoding Bruton's tyrosine kinase (btk) cause the B cell deficiency diseases X-linked agammaglobulinemia (XLA) in humans and X-linked immunodeficiency (xid) in mice. In vivo and in vitro studies indicate that the BTK protein is essential for B cell survival, cell cycle progression, and proliferation in response to B cell antigen receptor (BCR) stimulation. BCR stimulation leads to the activation of transcription factor nuclear factor (NF)-κB, which in turn regulates genes controlling B cell growth. We now demonstrate that a null mutation in btk known to cause the xid phenotype prevents BCR-induced activation of NF-κB. This defect can be rescued by reconstitution with wild-type BTK. This mutation also interferes with BCR-directed activation of IκB kinase (IKK), which normally targets the NF-κB inhibitor IκBα for degradation. Taken together, these findings indicate that BTK couples IKK and NF-κB to the BCR. Interference with this coupling mechanism may contribute to the B cell deficiencies observed in XLA and xid.